(untitled) (Global Journal of Medical Research, 2024)
Testicular seminoma commonly occurs in young men aged between 15 and 45 years old Those with testicular cancer may present with a lump or swelling in the testicle If treated and managed early patients can expect a greater than 90 success rate However advanced stages of testicular seminoma can lead to eventual metastasis We present a 45-year-old male patient with a prior history of testicular seminoma who was admitted to the emergency department with abdominal distension and mild abdominal pain The CT identified a rather sizable abdominal mass and the biopsy report confirmed metastatic testicular seminoma This patient is currently on active chemotherapy with bleomycin cisplatin and etoposide